Budgetary policy modelling: Public expenditures - Pantelis Capros; Danièle Meulders (Routledge, 1997)
The focus of this volume is on the European context of public budget policy and a variety of different approaches are used - theoretical modelling, econometrics and applied general equilibrium modelling. Empirical evidence and case studies of European countries are contained in all the papers. The papers cover the four general themes of public budget policy: * economic stabilization, in view of the Economic and Monetary Union in the European Community * reinforcing structural change, involved in market liberalization and harmonization of economic structures * its distributional effects and implications for social equity * endogenous economic growth.
Keywords: 330; Öffentlicher Haushalt; Öffentliche Ausgaben; Ökonometrie; Theorie; EU-Staaten